Naturally Tan - France, Tan (St. Martin's Press, 2019)
In this heartfelt, funny, touching memoir, Tan France tells his origin story for the first time. With his trademark wit, humor, and radical compassion, Tan reveals what it was like to grow up gay in a traditional South Asian family, as one of the few people of color in South Yorkshire, England. He illuminates his winding journey of coming of age, finding his voice (and style!), and marrying the love of his life<U+2015>a Mormon cowboy from Salt Lake City. From one of the stars of Netflix<U+2019>s runaway hit show Queer Eye, Naturally Tan is so much more than fashion dos and don<U+2019>ts<U+2015>though of course Tan can<U+2019>t resist steering everyone away from bootcut jeans! Full of candid observations about U.S. and U.K. cultural differences, what he sees when you slide into his DMs, celebrity encounters, and the behind-the-scenes realities of “reality TV,” Naturally Tan gives us Tan<U+2019>s unique perspective on the happiness to be found in being yourself.